2021
DOI: 10.1039/d1sm00130b
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of simple continuum models for diverse granular intrusions

Abstract: Granular intrusion is commonly observed in natural and human-made settings. Unlike typical solids and fluids, granular media can simultaneously display fluid-like and solid-like characteristics in a variety of intrusion scenarios....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
(117 reference statements)
1
17
0
Order By: Relevance
“…As the intrusion proceeds, the height of the frustum gradually increases, and at d = 0.10, the frustum eventually develops into a cone and maintains its shape afterward till the end of the intrusion at d = 2.0. This observation is in line with the postulation by Aguilar and Goldman, 59 while the "fanning out" mechanism of the wedge 60 has not been observed from our simulations.…”
Section: Intrusion Of Solid Objectsupporting
confidence: 93%
See 3 more Smart Citations
“…As the intrusion proceeds, the height of the frustum gradually increases, and at d = 0.10, the frustum eventually develops into a cone and maintains its shape afterward till the end of the intrusion at d = 2.0. This observation is in line with the postulation by Aguilar and Goldman, 59 while the "fanning out" mechanism of the wedge 60 has not been observed from our simulations.…”
Section: Intrusion Of Solid Objectsupporting
confidence: 93%
“…The same topic has attracted a series of interesting studies recently. [57][58][59][60] Figure 11 illustrates the simulation setup involving two types of intruders with a dimension of 1 m in both height and diameter: cylinder and cuboid. Given the symmetry nature of the problem, only one quarter of the domain is simulated with a dimension of 5 × 5 × 5 m. Figure 11B,C shows the mesh and the associated material points, respectively.…”
Section: Intrusion Of Solid Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it has been shown that plasticity-based PDE models can also obtain the form of 2D granular RFT (21). More recently, the performance of the continuum approach in modeling a variety of granular intrusions has been demonstrated for wheeled locomotion, impact and penetration, and multi-body intrusion (2,(22)(23)(24)(25). Additionally, the approach also provides insight into the somewhat surprising observation that granular RFT is often more accurate than its viscous fluid counterpart (12,13).…”
Section: Significance Statementmentioning
confidence: 99%